In a garden burning gold - Power, Rory (Argyrosi, 2022)
"Twins imbued with incredible magic and near-immortality will do anything to keep their family safe-even if it tears the siblings apart-in the first book of a mythic epic fantasy from the New York Times bestselling author of Wilder Girls. Rhea and her twin brother, Lexos, have spent an eternity helping their father rule their small, unstable country, using their control over the seasons, tides, and stars to keep the people in line. For a hundred years, they've been each other's only ally, defending each other and their younger siblings against their father's increasingly unpredictable anger. Now, with an independence movement gaining ground and their father's rule weakening, the twins must take matters into their own hands to keep their family-and their entire world-from crashing down around them. But other nations are jockeying for power, ready to cross and double cross, and if Rhea and Lexos aren't careful, they'll end up facing each other across the battlefield"--